Evaluation of antiplasmodial properties of a cyanobacterium, Spirulina platensis and its mechanism of action. Issue 17 (2nd September 2018) - Wulandari, Diah Anggraini; Sidhartha, Elizabeth; Setyaningsih, Iriani; Marbun, Jonathan Marshall; Syafruddin, Din; Asih, Puji Budi Setia
Abstract: The rapid emergence of antimalarial drug resistance necessitates a continual effort on novel drug discovery. A cyanobacterium, Spirulina platensis, is a potential antimalarial agent that has been widely consumed as food supplement in the form of crude extract. It is known to possess antiviral, antibacterial and antifungi activities. This study examined the antimalarial activities of several Spirulina formulas against Plasmodium falciparum 3D7, in vitro . The tested Spirulina formulas included commercially available capsule, crude extract and alkaloid fraction. Results showed that all tested formula possessed antimalarial activities with the Spirulina capsule exhibited the highest activities (IC50 = 2.16 μg/mL). Light and electron microscopies revealed interference of the Spirulina with the parasite hemozoin formation. In conclusion, all tested Spirulina formulas and fraction exhibited moderate to high antimalarial activities. Abstract :